2010
DOI: 10.1002/btpr.379
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthetic efficiency of Chlorella sorokiniana in a turbulently mixed short light‐path photobioreactor

Abstract: To be able to study the effect of mixing as well as any other parameter on productivity of algal cultures, we designed a lab-scale photobioreactor in which a short light path (SLP) of (12 mm) is combined with controlled mixing and aeration. Mixing is provided by rotating an inner tube in the cylindrical cultivation vessel creating Taylor vortex flow and as such mixing can be uncoupled from aeration. Gas exchange is monitored on-line to gain insight in growth and productivity. The maximal productivity, hence ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
84
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 135 publications
(96 citation statements)
references
References 48 publications
3
84
0
3
Order By: Relevance
“…Regarding the biomass yield on light (Y x/ph ), two values are depicted: 1.5 g-DW mol-ph -1 and a lesser value of 1.0 g-DW mol-ph -1 the first is the maximum biomass yield derived from our current comprehension of photosynthesis and the second is based on a range of dedicated studies. We believe 1.0 g-DW mol-ph -1 is a realistic aim for a large-scale microalgae production plant as this value is in the higher end of commonly measured biomass yields on light (Kliphuis et al 2010;Takache et al 2010;Vejrazka et al 2011;Zijffers et al 2010;Zittelli et al 2006). is selected as the maximum value in this graph.…”
Section: Electricity Costs Resulting From Artificial Lightingmentioning
confidence: 99%
“…Regarding the biomass yield on light (Y x/ph ), two values are depicted: 1.5 g-DW mol-ph -1 and a lesser value of 1.0 g-DW mol-ph -1 the first is the maximum biomass yield derived from our current comprehension of photosynthesis and the second is based on a range of dedicated studies. We believe 1.0 g-DW mol-ph -1 is a realistic aim for a large-scale microalgae production plant as this value is in the higher end of commonly measured biomass yields on light (Kliphuis et al 2010;Takache et al 2010;Vejrazka et al 2011;Zijffers et al 2010;Zittelli et al 2006). is selected as the maximum value in this graph.…”
Section: Electricity Costs Resulting From Artificial Lightingmentioning
confidence: 99%
“…The experiments by Miller et al (Miller et al, 1964) regarding a bioreactor with the Taylor vortex flow indicated that the rate of photosynthesis increases with an increasing rotor speed. Also, Kliphuis et al (Kliphuis et al, 2010) investigated the effects of the density of algae in the Taylor vortex flows on productivity. Also, it has been confirmed by Kawai (Kawai, 2010) that cell death is negligible in the range below the Reynold number based on the gap, d, between cylinders of Re = 30000, where the flow field was also measured by an ultrasonic Doppler velocity profiler.…”
mentioning
confidence: 99%
“…The theoretical maximum biomass yield on light (YCx/ph) for Chlorella sorokiniana with nitrate as nitrogen source is approximately 1.57 g molph -1 (Kliphuis et al 2010). …”
Section: Discussionmentioning
confidence: 99%